Alert and ready : an organizational design assessment of Marine Corps intelligence - Paul, Christopher, 1971- (Rand Corporation monograph series., 2011)
"As the U.S. Marine Corps (USMC) has grown in strength, it has needed to add intelligence capabilities. Since the end of the Cold War and, especially, since September 11, 2001, USMC intelligence has had to tailor its organization to meet the evolving demands of the operational environment. This has resulted in a number of ad hoc arrangements, practices, and organizations. A broad review of the organizational design of the USMC intelligence enterprise examined how to align it efficiently and effectively with current and future missions and functions. Specifically, the review, which included interviews with a range of USMC personnel and civilians, considered the organization of (and possible improvements to) the Intelligence Department, the Marine Corps Intelligence Activity, the intelligence organizations within the Marine Expeditionary Forces (specifically, the intelligence and radio battalions), and intelligence structures in the combat elements. A comparison of 48 organizational and functional issues with a series of USMC intelligence and functional issues resulted in a series of recommendations to help improve the "fit" of USMC intelligence organizations with their environmental context. In some cases, the service would benefit not from changing its intelligence structure but by realigning it; in other areas, restructuring would lend greater efficiency and effectiveness to the USMC intelligence enterprise."--Page 4 of cover.